Perceived anxiety and physical activity behaviour changes during the early stages of COVID-19 restrictions in community-dwelling adults in Canada: a cross-sectional study - Patricia K Doyle-Baker; Gavin R McCormack; Jennie A Petersen; Dalia Ghoneim (BMJ Open)
Objectives The COVID-19 pandemic changed daily routines, including physical activity, which could influence physical and mental health. In our study, we describe physical activity and sedentary behaviour patterns in relation to the pandemic and estimate associations between anxiety and physical activity and sedentary behaviour in community-dwelling adults.Design Cross-sectional study.Setting Calgary, Alberta, Canada.Participants Between April and June 2020, a random sample of 1124 adults (≥18 years) completed an online questionnaire.Primary and secondary outcomes The online questionnaire captured current walking, moderate intensity, vigorous intensity and total physical activity and sedentary behaviour (ie, sitting and leisure-based screen time), perceived relative changes in physical activity, sedentary and social behaviours since the pandemic, perceived seriousness and anxiety related to COVID-19, and sociodemographic characteristics. Differences in sociodemographic characteristics, perceived relative change in behaviour and current physical activity and sedentary behaviour were compared between adults with low and high anxiety.Results Our sample (n=1047) included more females (60.3%) and fewer older adults (19.2%). Most participants (88.4%) considered COVID-19 as extremely or very serious and one-third (32.9%) felt extremely or very anxious. We found no differences (p>0.05) in current physical activity or sedentary behaviour by anxiety level. The largest perceived change in behaviours included social distancing, driving motor vehicles, use of screen-based devices, watching television and interactions with neighbours. We found anxiety-related differences (p<0.05) in perceived changes in various behaviours.Conclusions Changes in physical activity, sedentary behaviour and social behaviour occurred soon after the COVID-19 pandemic was declared, and some of these changes differed among those with low and high anxiety.